Carbon fiber reinforced ceramic matrix composite resin carbon interface layer and preparation method thereof
Through the modification technology of KH-550 ratio solution and carboxylated carbon nanotubes, the problem of uneven thickness of the interface layer of carbon fiber reinforced ceramic matrix composite materials in the existing technology was solved. The liquid phase impregnation method and chemical bonding technology were used to prepare uniform The resin carbon interface layer improves the mechanical properties and service life of the material.
Patent Information
- Application Number
- CN202411138124.6
- Authority / Receiving Office
- CN · China
- Patent Type
- Applications(China)
- Current Assignee / Owner
- Filing Date
- 2024-08-19
- Publication Date
- 2024-12-31
AI Technical Summary
The existing liquid-phase permeation method has the problem of complex instruments, high cost and time-consuming, which leads to uneven thickness of the interface layer of carbon fiber reinforced ceramic matrix composite materials, affecting the mechanical properties and service life of the material.
Pretreated carbon fibers are impregnated with KH-550 ratio solution, and modified by carboxylated carbon nanotubes and combined with phenolic resin to form a uniform resin carbon interface layer. The liquid phase impregnation method and chemical bonding technology are used to ensure that the surface of the carbon fiber is uniformly covered with the interface. layer.
The preparation of carbon interface layer of carbon fiber reinforced ceramic matrix composite resin with simple process, low cost and short time is realized, and the interface bonding strength and the mechanical properties of the material are improved, and the load transfer and crack blocking functions are ensured.
Smart Images

Figure CN119221277A_ABST
Abstract
Description
Technical Field
[0001] The invention relates to the technical field of interface layer preparation, and in particular to a carbon fiber reinforced ceramic matrix composite material resin carbon interface layer and a preparation method thereof. Background Art
[0002] In recent years, due to the increasing demand for materials and increasingly demanding requirements in aerospace, automobile manufacturing, sports equipment, wind power, tidal power generation and other technical fields, carbon fiber reinforced ceramic matrix composites have overcome the stringent requirements and challenges in the above fields with their excellent performance and have been widely used. The two key factors affecting the mechanical properties of carbon fiber reinforced ceramic matrix composites are density and interface layer. Among them, the interface layer is an important component connecting the two phases of carbon fiber and silicon carbide. It plays the functions of load transfer, crack prevention, deflection and interface debonding. The mechanical properties of the composite material can be optimized by introducing the interface layer and heat treatment.
[0003] Since the carbon fiber surface active atom content is very small, the surface contains few active functional groups, and the bonding with the resin matrix is poor. The special properties of carbon fiber that are superior to other materials cannot be brought into play, resulting in a decrease in the overall performance of the composite material. Therefore, the interface problem of carbon fiber reinforced ceramic matrix composite materials needs to be solved urgently. At present, the commonly used pyrolytic carbon interface layer is mostly prepared by chemical vapor infiltration (CVI), while the preparation of carbon interface layer by phenolic resin as raw material with simple process and low cost is rarely reported. In addition, the CVI method has certain limitations on the size of components. For large thick-walled irregular components, during the CVI process, the diffusion rate of precursor gas molecules in the component is much lower than the chemical reaction rate due to the influence of the needle punching process pore structure and construction size of the 3D needle punched preform, which easily leads to uneven thickness of the outer surface and internal interface layer of the 3D needle punched fiber preform, and even incomplete internal deposition, forming an interface phase thickness gradient. The carbon interface layer of appropriate thickness improves the interface bonding strength of the composite material and increases the fracture energy dissipation path, thereby improving the strength and fracture toughness of the composite material. However, the uneven interface phase thickness gradient will seriously affect the mechanical properties stability and service life of the composite material.
[0004] In response to this phenomenon, some teams have tried to prepare an alternative phenolic resin interface layer, exploring the use of vacuum bag hot pressing technology to prepare carbon fiber / phenolic resin composites, and then heat treating them at 1100°C in a nitrogen atmosphere for 2 hours to prepare carbon / carbon composites. This method successfully produced a resin-carbon interface layer, but the method used is still complicated and not conducive to large-scale preparation. Summary of the invention
[0005] In order to solve the above technical problems, the purpose of the present invention is to provide a carbon fiber reinforced ceramic matrix composite resin carbon interface layer and a preparation method thereof, so as to solve the problems of complex equipment, high cost and time-consuming in the existing liquid phase infiltration method for preparing the resin carbon interface layer.
[0006] The technical solution of the present invention to solve the above technical problem is as follows: a method for preparing a resin-carbon interface layer of a carbon fiber reinforced ceramic matrix composite material is provided, comprising the following steps:
[0007] (1) dipping a carbon fiber preform in a KH-550 ratio solution, and then drying to obtain a pretreated carbon fiber preform;
[0008] (2) dispersing carbon nanotubes in a mixed acid, then keeping warm and centrifuging to obtain carboxylated carbon nanotubes;
[0009] (3) dispersing the carboxylated carbon nanotubes obtained in step (2) in a KH-550 ratio solution, adding the pretreated carbon fiber preform obtained in step (1), impregnating, and drying to obtain a carbon nanotube-modified carbon fiber preform;
[0010] (4) The carbon nanotube-modified carbon fiber preform obtained in step (3) is immersed in a phenolic resin ethanol solution, and then cured and cracked to obtain a carbon fiber reinforced ceramic matrix composite material resin carbon interface layer.
[0011] The beneficial effects of the present invention are as follows: the surface of the carbon fiber is chemically inert, and the surface of the carbon fiber is pretreated by impregnation with KH550. Since the KH550 solution has low surface tension and good wetting ability, it can be quickly spread on the surface of the carbon fiber; in addition, since the KH550 molecules are hydrolyzed in the solvent to generate Si-OH groups, these groups undergo condensation reaction on the surface of the carbon fiber to form a firmly bonded coating layer, and the -NH 2 The exposed -NH 2 The carbon fiber preform grafted with carbon nanotubes is further immersed in the phenolic resin solution to enhance the wettability of the phenolic resin on the carbon fiber surface. On the one hand, the phenolic resin molecules can react with the oxygen-containing functional groups on the carboxylated carbon nanotubes and the -NH exposed by KH-550. 2 On the other hand, the carbon fiber surface has carbon nanotubes to form a rough structure, which can be mechanically interlocked with the resin. The above impregnation process greatly ensures the effective coating of the phenolic resin interface layer on the carbon fiber surface.
[0012] The present invention uses a silane coupling agent to modify the carbon fiber surface and successfully introduces an amino active group, which can improve the wetting performance of the carbon fiber surface, help increase the amount of functionalized carbon nanotube grafting, and provide more active sites for the binding of phenolic resin, and the prepared resin carbon is more uniform and continuous. The resin carbon interface layer prepared based on chemical bonding has a suitable bonding strength with the carbon fiber surface, which can effectively transfer the load, hinder the crack extension and deflect the crack, thereby optimizing the performance of the composite material.
[0013] On the basis of the above technical solution, the present invention can also be improved as follows:
[0014] Furthermore, in steps (1) and (3), the KH-550 proportioning solution is a mixture of KH-550 and an organic solution; the organic solution is an alcohol solution, an aromatic hydrocarbon solution or an aliphatic hydrocarbon solution.
[0015] Furthermore, the organic solution is a methanol solution, an ethanol solution, an isopropanol solution, a n-butanol solution, a benzene solution, a toluene solution, a xylene solution, a butanone solution, an acetone solution or an ethyl acetate solution.
[0016] Furthermore, the organic solution is an ethanol solution.
[0017] Furthermore, the mass ratio of the KH-550 solution to the organic solution is 15-30:80-120.
[0018] Further, the concentration of the organic solution is 95 vt%.
[0019] Furthermore, in step (1), the mixture is dried at 75-85°C.
[0020] Further, drying was performed at 80°C.
[0021] Further, in step (2), the mixed acid is HNO with a mass ratio of 2.5-3.5:1 3 and H 2 SO 4 mixture.
[0022] Further, in step (2), the mixed acid is HNO with a mass ratio of 3:1 3 and H 2 SO 4 mixture.
[0023] Furthermore, in step (2), the carbon nanotubes have a length of 10-30 μm and a diameter of 20-50 nm.
[0024] Furthermore, in step (2), the temperature is kept at 65-75° C. for 1.8-2.2 h.
[0025] Furthermore, in step (2), the mixture is kept warm at 70° C. for 2 h.
[0026] Furthermore, in step (2), centrifugation is performed at 18000-22000 r / min for 8-12 min.
[0027] Furthermore, in step (2), centrifugation is performed at 20,000 r / min for 10 min.
[0028] Furthermore, in step (2), centrifugation is performed 2-5 times.
[0029] Furthermore, in step (3), the concentration of the carboxylated carbon nanotubes in the KH-550 mixed solution is 1-8 wt %.
[0030] Furthermore, in step (3), the drying conditions are the same as those in step (1).
[0031] Furthermore, in step (4), the concentration of the phenolic resin solution is 8-20 wt %.
[0032] Furthermore, in step (4), the solvent of the phenolic resin solution is ethanol.
[0033] Furthermore, in steps (1), (3) and (4), ultrasonic treatment is first performed for 0.4-0.6 h and then allowed to stand for 1-3 h to complete the impregnation process.
[0034] Furthermore, in steps (1), (3) and (4), ultrasonic treatment is first performed for 0.5 h and then allowed to stand for 1-3 h to complete the impregnation process.
[0035] Furthermore, in step (4), the curing is performed at 75-85°C for 1.8-2.2 hours, then at 95-105°C for 1.8-2.2 hours, then at 115-125°C for 1.8-2.2 hours, and finally at 145-155°C for 1.8-2.2 hours to complete the entire curing process.
[0036] Furthermore, in step (4), the whole curing process is completed by curing at 80°C for 2 hours, then at 100°C for 2 hours, then at 120°C for 2 hours, and finally at 150°C for 2 hours.
[0037] The invention also provides a carbon fiber reinforced ceramic matrix composite material resin carbon interface layer prepared by the method.
[0038] The present invention also provides application of the above interface layer in the preparation of ceramic-based composite materials.
[0039] The present invention has the following beneficial effects:
[0040] 1. The carbon fiber reinforced ceramic matrix composite resin carbon interface layer prepared by the present invention, as an important transition part connecting the carbon fiber and the matrix phase, plays a dual role of load transfer and fracture energy dissipation. The carbon fiber plays a bearing role, and the interface layer transfers the load on the silicon carbide matrix to the carbon fiber. The interface layer should have an appropriate interface strength to effectively transfer the load. When cracks appear in the silicon carbide matrix, the cracks extend to the interface layer, and the interface layer plays the role of crack blocking and expansion. Weak interface bonding can effectively hinder the expansion of cracks, but is not conducive to the transfer of loads. Appropriate interface bonding strength can not only effectively transfer loads, but also hinder crack expansion and deflect cracks, thereby optimizing the performance of the composite material.
[0041] 2. The resin carbon interface layer prepared by the method of the present invention has a simple process, short time consumption, adjustable thickness, and higher bonding strength with carbon fibers, which helps to improve the efficiency of interfacial stress transfer, inhibit fiber debonding, breakage and pull-out, has a short preparation cycle and low cost; it does not damage the carbon fibers and will not cause corrosion on the fiber surface.
[0042] 3. The liquid phase impregnation method adopted in the present invention is based on chemical bonding. The interface layer is combined with the carbon fiber through a certain chemical force, which can effectively optimize the mechanical properties of the composite material.
[0043] 4. The present invention can improve the uniformity of the carbon interface layer adhesion by adjusting the concentration of the functionalized carbon nanotube dispersion solution and the KH-550 ratio solution; and can also adjust the thickness of the carbon interface layer by adjusting the concentration of the phenolic resin solution, thereby obtaining a uniform resin carbon interface layer with adjustable thickness. BRIEF DESCRIPTION OF THE DRAWINGS
[0044] Figure 1 This is a scanning electron microscope image of the resin carbon interface layer prepared in Example 1. DETAILED DESCRIPTION
[0045] The principles and features of the present invention are described below in conjunction with the accompanying drawings. The examples are only used to explain the present invention and are not used to limit the scope of the present invention. If specific conditions are not specified in the embodiments, they are carried out according to normal conditions or conditions recommended by the manufacturer. If the manufacturer is not specified for the reagents or instruments used, they are all conventional products that can be purchased commercially.
[0046] Embodiment 1:
[0047] A carbon fiber reinforced ceramic matrix composite material resin carbon interface layer, the preparation method of which comprises the following steps:
[0048] (1) The carbon fiber preform is immersed in a KH-550 ratio solution (a mixture of KH-550 and ethanol solution with a mass ratio of 2:9, and the concentration of the ethanol solution is 95vt%), first ultrasonicated for 0.5h, then allowed to stand for 2h to complete the impregnation process, taken out, and dried at 80°C to obtain a pretreated carbon fiber preform;
[0049] (2) Carbon nanotubes (length 20 μm, diameter 35 nm) were dispersed in a mixed acid (HNO with a mass ratio of 3:1). 3 and H 2 SO 4 The mixture was then kept at 70° C. for 2 h, centrifuged at 20,000 r / min for 10 min, centrifuged 5 times, and collected to obtain carboxylated carbon nanotubes;
[0050] (3) dispersing the carboxylated carbon nanotubes obtained in step (2) in a KH-550 solution (a mixture of KH-550 and ethanol in a mass ratio of 2:9), wherein the concentration of the dispersed carboxylated carbon nanotubes is 1.5 wt %, and adding the pretreated carbon fiber preform obtained in step (1) for impregnation, first ultrasonicating for 0.5 h, then standing for 2 h to complete the impregnation process, and drying at 80° C. to obtain a carbon nanotube-modified carbon fiber preform;
[0051] (4) The carbon nanotube-modified carbon fiber preform obtained in step (3) is immersed in a phenolic resin ethanol solution (concentration of 15wt%), first ultrasonicated for 0.5h, then allowed to stand for 2h to complete the impregnation process, taken out, cured at 80°C for 2h, then cured at 100°C for 2h, then cured at 120°C for 2h, and finally cured at 150°C for 2h to complete the entire curing process, and cracked to obtain a carbon fiber reinforced ceramic matrix composite resin carbon interface layer.
[0052] Embodiment 2:
[0053] A carbon fiber reinforced ceramic matrix composite material resin carbon interface layer, the preparation method of which comprises the following steps:
[0054] (1) The carbon fiber preform is immersed in a KH-550 ratio solution (a mixture of KH-550 and ethanol solution with a mass ratio of 15:80, and the concentration of the ethanol solution is 95vt%), first ultrasonically treated for 0.4h, then allowed to stand for 1h to complete the immersion process, and then taken out and dried at 80°C to obtain a pretreated carbon fiber preform;
[0055] (2) Disperse carbon nanotubes in a mixed acid (HNO with a mass ratio of 2.5:1) 3 and H 2 SO 4The mixture was then kept at 65° C. for 2.2 h, centrifuged at 18000 r / min for 12 min, centrifuged twice, and collected to obtain carboxylated carbon nanotubes;
[0056] (3) dispersing the carboxylated carbon nanotubes obtained in step (2) in a KH-550 solution (a mixture of KH-550 and ethanol in a mass ratio of 15:80), wherein the concentration of the dispersed carboxylated carbon nanotubes is 1 wt%, and adding the pretreated carbon fiber preform obtained in step (1) for impregnation, first ultrasonicating for 0.4 h, then standing for 1 h to complete the impregnation process, and drying at 75° C. to obtain a carbon nanotube-modified carbon fiber preform;
[0057] (4) The carbon nanotube-modified carbon fiber preform obtained in step (3) is immersed in a phenolic resin ethanol solution (concentration is 8wt%), first ultrasonicated for 0.4h, then allowed to stand for 1h to complete the impregnation process, taken out, cured at 75°C for 2.2h, then cured at 95°C for 2.2h, then cured at 115°C for 2.2h, and finally cured at 115°C for 2.2h to complete the entire curing process, and cracked to obtain a carbon fiber reinforced ceramic matrix composite resin carbon interface layer.
[0058] Embodiment 3:
[0059] A carbon fiber reinforced ceramic matrix composite material resin carbon interface layer, the preparation method of which comprises the following steps:
[0060] (1) The carbon fiber preform was immersed in a KH-550 solution (a mixture of KH-550 and ethanol solution with a mass ratio of 30:120, and the concentration of the ethanol solution was 95vt%), firstly ultrasonicated for 0.6h, then allowed to stand for 3h to complete the immersion process, and then taken out and dried at 85°C to obtain a pretreated carbon fiber preform;
[0061] (2) Disperse carbon nanotubes in a mixed acid (HNO with a mass ratio of 3.5:1) 3 and H 2 SO 4 The mixture was then kept at 75° C. for 1.8 h, centrifuged at 22000 r / min for 8 min, centrifuged twice, and collected to obtain carboxylated carbon nanotubes;
[0062] (3) dispersing the carboxylated carbon nanotubes obtained in step (2) in a KH-550 solution (a mixture of KH-550 and ethanol in a mass ratio of 30:120), wherein the concentration of the dispersed carboxylated carbon nanotubes is 8 wt %, and adding the pretreated carbon fiber preform obtained in step (1) for impregnation, first ultrasonicating for 0.6 h, then standing for 3 h to complete the impregnation process, and drying at 85° C. to obtain a carbon nanotube-modified carbon fiber preform;
[0063] (4) The carbon nanotube-modified carbon fiber preform obtained in step (3) is immersed in a phenolic resin ethanol solution (concentration is 20wt%), first ultrasonicated for 0.6h, then allowed to stand for 3h to complete the impregnation process, taken out, cured at 85°C for 1.8h, then cured at 105°C for 1.8h, then cured at 125°C for 1.8h, and finally cured at 155°C for 1.8h to complete the entire curing process, and cracked to obtain a carbon fiber reinforced ceramic matrix composite resin carbon interface layer.
[0064] Test example
[0065] 1. The interface layer prepared in Example 1 was tested by scanning electron microscope. The results are shown in Figure 1 .
[0066] Depend on Figure 1 It can be seen that the resin carbon interface layer is evenly coated on the fiber surface, and the thickness of the interface layer ranges from 350-600nm. The overall thickness is uniform and the coating is complete. Due to the liquid phase impregnation method, there is almost no requirement for the structure and thickness of the impregnated component. The resin carbon interface layer plays a good role in protecting the fiber.
[0067] The above description is only a preferred embodiment of the present invention and is not intended to limit the present invention. Any modifications, equivalent substitutions, improvements, etc. made within the spirit and principle of the present invention should be included in the protection scope of the present invention.
Claims
1. A method for preparing a carbon fiber reinforced ceramic matrix composite resin carbon interface layer, characterized in that: The following steps are involved: (1) dipping a carbon fiber preform in a KH-550 ratio solution, and then drying to obtain a pretreated carbon fiber preform; (2) dispersing carbon nanotubes in a mixed acid, then keeping warm and centrifuging to obtain carboxylated carbon nanotubes; (3) dispersing the carboxylated carbon nanotubes obtained in step (2) in a KH-550 ratio solution, adding the pretreated carbon fiber preform obtained in step (1), impregnating, and drying to obtain a carbon nanotube-modified carbon fiber preform; (4) The carbon nanotube-modified carbon fiber preform obtained in step (3) is impregnated in a phenolic resin solution, and then cured and cracked to obtain a carbon fiber reinforced ceramic matrix composite material resin carbon interface layer.
2. The method for preparing a carbon fiber reinforced ceramic matrix composite resin carbon interface layer according to claim 1, characterized in that: In steps (1) and (3), the KH-550 proportioning solution is a mixture of KH-550 and an organic solution; the organic solution is an alcohol solution, an aromatic hydrocarbon solution or an aliphatic hydrocarbon solution.
3. The method for preparing the carbon fiber reinforced ceramic matrix composite resin carbon interface layer according to claim 1, characterized in that: In step (1), drying is performed at 75-85°C.
4. The method for preparing a carbon fiber reinforced ceramic matrix composite resin carbon interface layer according to claim 1, characterized in that: In step (2), the mixed acid is a mixture of HNO3 and H2SO4 in a mass ratio of 2.5-3.5:
1.
5. The method for preparing a carbon fiber reinforced ceramic matrix composite resin carbon interface layer according to claim 1, characterized in that: In step (3), the concentration of carboxylated carbon nanotubes in the KH-550 mixed solution is 1-8 wt %.
6. The method for preparing a carbon fiber reinforced ceramic matrix composite resin carbon interface layer according to claim 1, characterized in that: In step (4), the concentration of the phenolic resin solution is 8-20wt%.
7. The method for preparing a carbon fiber reinforced ceramic matrix composite resin carbon interface layer according to claim 1, characterized in that: In steps (1), (3) and (4), ultrasonic treatment is first performed for 0.4-0.6 h, and then allowed to stand for 1-3 h to complete the impregnation process.
8. The method for preparing a carbon fiber reinforced ceramic matrix composite resin carbon interface layer according to claim 1, characterized in that: In step (4), the curing is carried out at 75-85°C for 1.8-2.2 hours, then at 95-105°C for 1.8-2.2 hours, then at 115-125°C for 1.8-2.2 hours, and finally at 145-155°C for 1.8-2.2 hours to complete the entire curing process.
9. A carbon fiber reinforced ceramic matrix composite material resin carbon interface layer obtained by the method for preparing a carbon fiber reinforced ceramic matrix composite material resin carbon interface layer according to any one of claims 1 to 8.
10. Use of the carbon fiber reinforced ceramic matrix composite resin carbon interface layer according to claim 9 in the preparation of ceramic matrix composite materials.
